Pengaruh Kompensasi dan Lingkungan Kerja terhadap Turnover Intention Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening pada PT. Pancaran Energi Transportasi - Reza, Syah; Sitorus, Guston; Wijaya, Robby (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This study aims to analyze the influence of compensation and work environment on turnover intention, with job satisfaction as an intervening variable, among drivers/helpers at PT. Pancaran Energy Transportasi. The research employs a quantitative approach with a population of 114 drivers/helpers in the company. The analysis method used is path analysis, utilizing a Likert scale in the questionnaire. The research results indicate that compensation and work environment have a positive and significant impact on job satisfaction. Compensation also has a positive and significant effect on turnover intention, while the work environment does not have a direct significant impact on turnover intention. Job satisfaction also does not have a direct significant impact on turnover intention. Furthermore, compensation and work environment directly and significantly influence turnover intention through job satisfaction.